Sosialisasi Pemberdayaan UMKM Sektor Pariwisata Di Kabupaten Simalungun - Darwin Damanik; Pandapotan Damanik (Lembaga Pengembangan Kinerja Dosen, 2024)
The tourism sector in Simalungun Regency has enormous potential to grow, and the empowerment of MSMEs in this sector will not only contribute to the local economy but also encourage sustainable tourism practices. The purpose of this community service activity is to socialize the empowerment of tourism sector MSMEs in Simalungun Regency. The socialization method used was lecture and response with the participants of this activity being MSMEs around Paris Beach, Nagori Tiga Ras, Simalungun Regency. The results of this Community Service activity are first, the development of Tourism MSME businesses or tourist attractions in improving the welfare of the community and MSMEs must begin to be developed towards sustainable tourism supported by local governments through sustainable and useful programs. Second, the understanding of MSMEs around the outskirts of the Lake Toba area regarding Regional Regulation No. 1 of 1990 which is still a problem for MSMEs in Paris Beach